Evaluation of the implementation effect of hepatitis C medical insurance reimbursement policy in China: A RWS based on medical institutions - Liu, Yiyao; Gou, Liangwen; Guo, Zhaoting; Wu, Zhiang; He, Qin; Feng, Haihuan; Hu, Ming (Frontiers in Public Health, 2023)
Objectives To evaluate the implementation effect of hepatitis C medical insurance reimbursement policy in China from the view of medical institutions. Methods The electronic medical record of a top tertiary hospital in Chengdu from January 2014 to December 2020 were extracted, and the interrupted time series model was used to analyze the changes in diagnosis and treatment behavior and disease burden of hepatitis C patients after the implementation of HCV insurance reimbursement policy. Results In terms of diagnosis and treatment, the number of visits (β2 = 19.290, P < 0.001) and treatments (β2 = 14.291, P < 0.01) increased instantaneously after the implementation of the outpatient reimbursement policy in Chengdu in 2018, and there was no significant change after the implementation of the single line payment policy for oral direct antiviral (DAA) drugs in 2019 (P > 0.05); in terms of medical expenses, the total treatment cost (β2 = 21439.3, P < 0.001), out-of-pocket expenses (β2 = 6109.44, P < 0.001) and drug expenses (β2 = 21889.8, P < 0.001) of hepatitis C patients have been significantly reduced after the implementation of the single-line payment policy. Conclusion Hepatitis C medical insurance reimbursement policy can promote hepatitis C patients to actively seek medical treatment, promote the widespread use of DAA scheme, reduce the burden of patients, and improve the treatment efficiency of hepatitis C.